Lutetium 177-DOTA-TATE therapy for esthesioneuroblastoma: A case report - Sabongi, Juliano Guerra; Pereira Goncalves, Monica Carboni; Casado Alves, Cira Danielle; Alves, Joao; Scapulatempo-Neto, Cristovam; Moriguchi, Sonia Marta [UNESP] (Spandidos Publ Ltd, 2016)
Esthesioneuroblastoma (ENB), also known as olfactory neuroblastoma, is a rare malignant tumor that accounts for 3% of all tumors of the nasal cavity. The incidence of ENB is 0.4 cases per million in the general population, and the most common symptoms are nasal obstruction and epistaxis. Previous studies have indicated the presence of somatostatin receptors in this tumor type. Common treatment strategies for ENB include resection and adjuvant radiotherapy and/or chemotherapy (combined treatment); however, the rate of recurrence is high. Treatment of neuroendocrine tumors using radionuclides bound to somatostatin analogues is well established in clinical practice. However, a standard and effective therapeutic approach has not been reported for ENB. The current study described the case of a 74-year-old female with numerous recurrences of ENB following multiple treatments and without possibility of resection. The patient was treated with the radiolabeled-somatostatin analogue, (177)Lutetium-DOTA-octreotate (Lu-177-DOTA-TATE), which successfully controlled the disease. This suggests that Lu-177-DOTA-TATE is a potential treatment for ENB and may represent an effective alternative and novel therapeutic strategy for this disease.
Keywords: esthesioneuroblastoma; lutetium 177; neuroendocrine tumors; olfactory neuroblastoma; nuclear medicine; radioisotopes